The Nordic Banking Crises : Pitfalls in Financial Liberalization? - Drees, Burkhard (IMF Working Papers; Working Paper, 1995)
This paper examines the recent banking crises in Finland, Norway and Sweden in an attempt to draw some policy conclusions from their experiences. In all three countries, the timing of deregulation coincided with a strongly expansionary macroeconomic momentum. Delayed policy responses, as well as structural characteristics of the financial systems, and banks' inadequate internal risk management controls were important determinants of the consequences of the transition from tightly regulated to more or less competitive financial systems. In the absence of strengthened prudential banking supervision, these incentives coupled with expectations of government intervention in the event of a crisis prompted many Nordic banks to increase their lending excessively.